2003
DOI: 10.1177/088532803038026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of c-Sterilization Process on PLGA Microspheres Loaded with Insulin-Like Growth Factor - I (IGF-I)

Abstract: The influence of gamma-sterilization on the physicochemical properties of a controlled release formulation for the insulin-like growth factor-I (IGF-I) was investigated in this study. Recombinant human insulin-like growth factor-I (rhIGF-I) was efficiently entrapped in poly (D,L-lactide-co-glycolide) (PLGA) microspheres by water-in-oil-in-water (W/O/W) solvent evaporation technique. Microspheres were irradiated at a dose of 25kGy and evaluated by means of scanning electron microscopy (SEM) and differential sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Calculation of the similarity factor (f 2 ) between both release profiles gave a value lower than 50 (37.47), thereby indicating that the release profiles cannot be considered similar. Other authors have also shown that γ-irradiation affected the drug release rate 31 . For instance PLGA decomposition and the decrease in the average molecular weight increased both the extent and the rate of bupivacaine released from PLGA microspheres 32 .…”
Section: Resultsmentioning
confidence: 94%
“…Calculation of the similarity factor (f 2 ) between both release profiles gave a value lower than 50 (37.47), thereby indicating that the release profiles cannot be considered similar. Other authors have also shown that γ-irradiation affected the drug release rate 31 . For instance PLGA decomposition and the decrease in the average molecular weight increased both the extent and the rate of bupivacaine released from PLGA microspheres 32 .…”
Section: Resultsmentioning
confidence: 94%
“…Other studies reported that the osteoinductive potential of bone morphogenetic proteins of various origins was preserved after sterilization at 25 kGy (27,28). Growth factors react differently to gamma irradiation: gamma sterilization alters the properties of insulin-like growth factor-1 (29), whereas the TGF-β superfamily is resistant to high doses of radiation. Our data suggest that gamma irradiation does not activate, but rather maintains, the intrinsic activity of BCM to induce changes in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The process can be undertaken with a wide range of polymers, and is relatively easy to scale-up (Iqbal et al, 2015). The oil-in-water emulsion and double emulsion (w 1 /o/w 2 ) methods are most widely explored, although sterilization can be challenging and low encapsulation efficacy can be an issue as proteins are able to diffuse from the oil phase to the continuous aqueous phase (Carrascosa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%